Welcome to the oops club!: Varied patterns of mistake responses in a veteran teacher’s classroom - Donaldson, Maleka (Frontiers in Education, 2023)
This study explores the range of distinct mistake responses that one veteran public-school teacher employs with her class of 20 Kindergarten students during daily learning and teaching. Relying on more than 60 hours of classroom observations and using a grounded theory approach, a micro-level, qualitative analysis of the teacher's responses to each child's mistakes was conducted, attending to words and actions during instructional interactions captured in fieldnotes and video recordings. Data analysis of observed teaching practices revealed five distinct patterns that the teacher used to help children correct academic and/or behavioral mistakes. The amount and type of teacher involvement ranged from little engagement with mistakes for students who rarely made any, to heavy-handed supports for children who routinely struggled to obtain right answers.